The Material Conditions of Experience: The Specification of the Concept of Matter in the Critique of Pure Reason - Pelegrin, Laura Alejandra (2025)
The aim of our research is to exhibit the characterization of the material conditions of experience in the Critique of Pure Reason. We argue that, in conjunction with the study of the formal conditions of experience, Kant indirectly addresses the problem of the material conditions. We will show how the concept of matter is specified throughout the Critique of Pure Reason. Kant demonstrates that, just as we possess specific formal conditions that make experience possible, specific material conditions are also necessary for experience to occur.